Comment on Activity 7

The third side of the triangle in Figure 4 is `sqrt(1-x^2)`, so this is also `cos y`.

`d/(dx) sin y`
`=d/(dx) x`
`cos y (dy)/(dx)`
`=1`
`(dy)/(dx)`
`=1/(cos y)`
`(dy)/(dx)`
`=1/sqrt(1-x^2)`
We differentiate implicitly the formula `sin y=x`, where `y=sin^(-1) x:`


 

 

 

 

 

`(dy)/(dx)`
`=1/((dx)/(dy))`
  `=1/(d/(dy) sin y)`
  `=1/(cos y)`
  `=1/sqrt(1-x^2)`
Thus, `d/(dx) sin^(-1) x=1/sqrt(1-x^2)`. Now we see that the inverse function formula leads to the same result: